AGE PECULIARITIES OF MORPHOFUNCTIONAL CHANGES OF THE LIVER AT EARLY STAGES OF DIABETES MELLITUS DEVELOPMENT WITH THE USE OF CLUSTER ANALYSIS - Zhurakivska, O.Ya.; Боднарчук, Ю.В.; Oliinyk, R.P.; Miskiv, V.A.; Andriiv, A.V. (World of Medicine and Biology, 2021)
In all age groups of animals, we observed regular changes in the morphometric parameters of hepatocytes of different clusters: there was a decrease in the area of hepatocytes, which is associated with marked processes of glycogenolysis that are confirmed by histological and ultrastructural studies. On the14 th and 28 th days of diabetes mellitus, as compared to the control group, the number of hepatocytes in clusters varies: in rats aged 24 months in С1 and С3 it decreases by 8–7 % and 6-10 %, whereas in С2 it increases by 14–17 %. In rats aged 12 months, as compared with the control group of animals, on the14th day, the number of hepatocytes in C1 decreased by 3.64 %, while in C2 it increases by 5.37 %, while on the 28th day in C2 it decreases by 3.69 %, while in C3 it increases by 4.81 % (in all cases р
Keywords: liver; hepatocyte; streptozotocin-induced diabetes mellitus